IMPLEMENTASI KEBIJAKAN RETRIBUSI PASAR DI PASAR PUNI KABUPATEN MANGGARAI PROVINSI NUSA TENGGARA TIMUR (JURNAL ADMINISTRASI PUBLIK, 2020)
This research aims to find out how the implementation of the policy of market retribution in Punimarket of Manggarai district. This research uses qualitative method involving 6 informant thatconsists of the responsibility of the local levy, implementing market retribution policy and tradersin the market, Manggarai district.Data collection is done by interview, observation and documentation. The results showed that theimplementation of the policy of market retribution in Puni market of Manggarai district, explainedthat the implementation of the policy on market retribution was in accordance with the prevailingrules and regulations. The importance of this policy is deemed to conform to the interests of thetarget group. There are only a few obstacles that make this policy goal still difficult to achieve. Oneof the most dominant problems of the findings in this study is the lack of public awareness about thebenefits and importance of retribution. Therefore, it takes more effort from the implementingauthorities to address these issues so that policy objectives can be achieved.Key Words: Implementation of Policy, Market Retribution, Trader.